Modern perspectives in lattice QCD quantum field theory and high performance computing : lecture notes of the Les Houches Summer School, Volume 93, August 2009 - n; Lellouch, Laurent (Oxford : Oxford University Press, 2011)
The aim of this title is to familiarise the new generation of PhD students and postdoctoral fellows with the principles and methods of modern lattice field theory, which aims to resolve fundamental, non-perturbative questions about QCD without uncontrolled approximations.
Description based on print version record.
Keywords: Lattice field theory -- Congresses; Quantum field theory -- Congresses